2001
DOI: 10.1073/pnas.091062498
|View full text |Cite
|
Sign up to set email alerts
|

Significance analysis of microarrays applied to the ionizing radiation response

Abstract: Microarrays can measure the expression of thousands of genes to identify changes in expression between different biological states. Methods are needed to determine the significance of these changes while accounting for the enormous number of genes. We describe a method, Significance Analysis of Microarrays (SAM), that assigns a score to each gene on the basis of change in gene expression relative to the standard deviation of repeated measurements. For genes with scores greater than an adjustable threshold, SAM… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

46
9,658
2
66

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10,435 publications
(9,772 citation statements)
references
References 30 publications
46
9,658
2
66
Order By: Relevance
“…To determine the significant pharmacological response to treatment, we performed a paired analysis using significance analysis of microarrays. 33 A gene was considered as significantly differential expressed if the false discovery rate was equal to or o5%. Cluster analysis 34 was used to define clusters of co-coordinately changed genes after which the data were visualized using Treeview (http://rana.lbl.gov/ EisenSoftware.htm).…”
Section: Pharmacogenomics Of Infliximab Treatmentmentioning
confidence: 99%
“…To determine the significant pharmacological response to treatment, we performed a paired analysis using significance analysis of microarrays. 33 A gene was considered as significantly differential expressed if the false discovery rate was equal to or o5%. Cluster analysis 34 was used to define clusters of co-coordinately changed genes after which the data were visualized using Treeview (http://rana.lbl.gov/ EisenSoftware.htm).…”
Section: Pharmacogenomics Of Infliximab Treatmentmentioning
confidence: 99%
“…We also compare our method with SAM using the same dataset for NSCLC lung cancer. SAM combines t-test and permutations to calculate a False Discovery Rate to provide a subset of genes that are considered significant [16]. Using SAM, we select four sets of 50, 100, 150, 200 and 250 most significant genes by using the parameter values of 0.556.…”
Section: Resultsmentioning
confidence: 99%
“…Comparing with recent publications in that the authors use currently available data mining techniques to find biomarkers for NSCLC lung cancer, we found that our new method finds significantly more cost-effective genetic markers and provides more accurate sub-classification of NSCLC lung cancer. Comparison with SAM [16], a popular method for significance analysis of microarrays, is also provided in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…Significance analysis of microarray (SAM)26 was used to analyze gene expression difference by between high‐TRIM26‐NPCs and low‐TRIM26‐NPCs, and high‐TRIM26‐NPs and low‐TRIM26‐NPCs. The delta was set to 0.94 so that false discovery rate (FDR) was 5% for each group comparison.…”
Section: Methodsmentioning
confidence: 99%